2014
DOI: 10.4155/bio.14.26
|View full text |Cite
|
Sign up to set email alerts
|

Breath Analysis of Ammonia, Volatile Organic Compounds and Deuterated Water Vapor in Chronic Kidney Disease and During Dialysis

Abstract: The volatile metabolites present in trace amounts in exhaled breath of healthy individuals and patients, for example those with advanced chronic kidney disease (CKD), can now be detected and quantified by sensitive analytical techniques. In this review, special attention is given to the major retention metabolites resulting from dialysis-dependent CKD stage 5 and especially ammonia, as a potential estimator of the severity of uremia. However, other biomarkers are important, including the hydrocarbons isoprene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 109 publications
0
40
0
Order By: Relevance
“…However, some have now demonstrated effective application in human clinical studies (Hibbard et al, 2013). Several reviews are available on ammonia measurement techniques (Davies et al, 2014;Hibbard and Killard, 2011;Spanel and Smith, 2011). However, this is not the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…However, some have now demonstrated effective application in human clinical studies (Hibbard et al, 2013). Several reviews are available on ammonia measurement techniques (Davies et al, 2014;Hibbard and Killard, 2011;Spanel and Smith, 2011). However, this is not the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…The value of SIFT-MS real time analysis has also been well demonstrated by, for example, studies of breath ethanol and its metabolite acetaldehyde following the ingestion of alcohol [39] and by the TBW studies mentioned above [34,41]. Nose/mouth exhaled breath studies can also distinguish between truly endogenous (systemic) compounds and those predominantly generated in the oral cavity, which is a necessary requirement as the topic of breath research progresses towards meaningful clinical diagnosis and therapeutic monitoring, as promoted and accelerated by the work of Professor Anton Amann to whose memory this paper is humbly and affectionately dedicated.…”
Section: Discussionmentioning
confidence: 86%
“…By using the principle of isotope dilution together with the quantity of D2O ingested, the total body water, TBW, of an individual can be determined on-line and in real time by analysing single breath exhalations. Thus, the TBW of several cohorts of patients and healthy controls [144] have been measured in the clinical setting using FA-MS, [44,145,146], including patients suffering from chronic kidney disease who naturally suffer from water overload [147][148][149] and to whom such studies have been especially focused. It has been shown that this FA-MS method of measuring TBW is both feasible in a busy renal unit and acceptable to patients attending the dialysis clinic [150,151].…”
Section: Sift-msmentioning
confidence: 99%